2-Phenethyl isothiocyanate, glutathione S-transferase M1 and T1 polymorphisms, and detoxification of volatile organic carcinogens and toxicants in tobacco smoke - Yuan, Jian-Min (Cancer Prev Res (Phila), 2016)
Cigarette smoke contains relatively large quantities of volatile organic toxicants or carcinogens such as benzene, acrolein and crotonaldehyde. Among their detoxification products are mercapturic acids formed from glutathione conjugation, catalyzed in part by glutathione S-transferases (GST). A randomized phase 2 clinical trial with a crossover design was conducted to evaluate the effect of 2-phenethyl isothiocyanate (PEITC), a natural product formed from gluconasturtiin in certain cruciferous vegetables, on the detoxification of benzene, acrolein, and crotonaldehyde in 82 cigarette smokers. Urinary mercapturic acids of benzene, acrolein and crotonaldehyde at baseline and during treatment were quantified. Overall, oral PEITC supplementation increased the mercapturic acid formed from benzene by 24.6% (P=0.002) and acrolein by 15.1% (P=0.005), but had no effect on crotonaldehyde. A remarkably stronger effect was observed among subjects with the null genotype of both GSTM1 and GSTT1: in these individuals PEITC increased the detoxification metabolite of benzene by 95.4% (P<0.001), of acrolein by 32.7% (P=0.034), and of crotonaldehyde by 29.8% (P=0.006). In contrast, PEITC had no effect on these mercapturic acids in smokers possessing both genes. PEITC had no effect on the urinary oxidative stress biomarker 8-iso-prostaglandin F(2α) or the inflammation biomarker prostaglandin E(2) metabolite. This trial demonstrates an important role of PEITC in detoxification of environmental carcinogens and toxicants which also occur in cigarette smoke. The selective effect of PEITC on detoxification in subjects lacking both GSTM1 and GSTT1 genes supports the epidemiological findings of stronger protection by dietary isothiocyanates against the development of lung cancer in such individuals.